Download presentation
Presentation is loading. Please wait.
Published byRalph Horn Modified over 8 years ago
2
The change of base property can be summarized in one equation: log a (x) = log b (x)/log b (a) This property is often essential for simplifying logarithms. In particular, we often have to use it to put logarithms in a form we can solve with our calculators.
3
Let x = b y and let a = b z. Raise each side of the second equation to the power (y/z). By the properties of exponents, this gives us a y/z = b z(y/z), which is equivalent to a y/z = b y. We know that b y = x, so we substitute x into the equation. We now have x = a y/z. By taking the log base a of both sides, we are left with log a (x) = y/z. From the first two equations, y = log b (x) and z = log b (a). Thus, we can substitute for y and z, leaving log a (x) = log b (x)/log b (a).
4
Using a calculator, calculate the value of log 5 9.
5
Our calculator probably doesn’t have a function for logarithms of base 5, so we need to swap our base to something we can use, like e. Using the change of base property, log 5 (9) = ln(9)/ln(5) ≈ 2.2/1.6 = 1.38.
Similar presentations
© 2025 SlidePlayer.com. Inc.
All rights reserved.